Two photos of the 'weiblichen Abgeordneten der soziald. Fraktion zur Nationalversammlung 1919 Weimar' with place of persons indicated on back of photos
Two photos of the 'weiblichen Abgeordneten der soziald. Fraktion zur Nationalversammlung 1919 Weimar' with place of persons indicated on back of photos.